Judicial reform and economic development : a survey of the issues - Messick, Richard E. (1999)
Surveys a wide range of current studies on judicial reform. Concludes that in the absence of better theoretical understanding of the impact of judicial reform, care is required in designing and implementing projects. Notes that reform must be preceded by an in-depth analysis of country needs - an analysis that must be continually reviewed as implementation proceeds.